The athlete/coach relationship in competitive swimming: the implications of personality type, temperament type and coach evaluation - Vikander, N. O.; Stallmann, R. K.; Soyland, B. (Biomechanics and Medicine in Swimming. Swimming Science VI, 1992)
Personality profiles of 53 coaches and 163 competitive swimmers in Norway were mapped using the Myers-Briggs Type Indicator (MBTI). Distribution patterns of swimmers and coaches varied greatly indicating different recruitment and retention factors. Twenty of the coaches were evaluated by their swimmers using the Coach Evaluation Questionnaire (CEQ). The degree of coach/swimmer personality similarity was compared with CEQ scores using Spearman's rank order correlation. Significance was found (rho = 0.440) on an integrative measure but not on separate elements of personality. The CEQ scores indicate strong organizational skills but weaker human relations capacities. Results suggest a programme of selfdevelopment for coaches using MBTI/CEQ profiles as points of departure.